Upaya Guru PPKN Untuk Meningkatkan Minat Belajar Terhadap Peserta Didik Yang Kecanduan Media Sosial Di MTS Miftahul Ulum Banyuanyar Lor Kabupaten Probolinggo - Madaniatus Silviah; Nurul Saila; Ludfi Arya Wardana (CV. ITTC INDONESIA, 2023)
The problem in this study is caused by social media addiction which can affect student learning interest at MTs Miftahul Ulum Banyuanyar Lor, Probolinggo District. This study aims to describe the efforts of Civics teachers to increase learning interest in students who are addicted to social media. The research method uses a qualitative approach with interview and observation data collection techniques. The research subjects included PPKn teachers and class VIII students. From the results of the study it was found that the efforts of Civics teachers to increase learning interest in students who are addicted to social media, namely by building students' interest in learning, can make the class atmosphere fun and not boring in conveying learning material so that it is efficient. Of the various solutions that have been implemented, there are several solutions that have not yet been implemented. This is due to the difficulties in accessing social media which are still being implemented and are trying to provide the best facilities. The conclusion from this study is that PPKn teachers must be able to provide learning motivation at the beginning and at the end of learning, provide interesting learning media, namely the only way to take advantage of the convenience of accessing social media and also that the school will work with parents of students to control students in playing media social at home.